A functionalist typology of redundancy - Leufkens, Sterre (Revista da ABRALIN, 2020)
Syntagmatic redundancy involves the multiple expressions of a single meaning within a phrase or clause. It is often claimed to be a linguistic universal that serves to facilitate expressivity, processing, and learnability. However, there is little empirical evidence supporting this theory. This paper combines a typological study of concord, a form of syntagmatic redundancy in which a lexical and a grammatical item with overlapping meanings are expressed in the same phrase or clause, with a functional analysis of concord. The purpose of the study was to find out if redundancy is indeed universal or whether there are cross-linguistic restrictions. The goal of the functional analysis was to provide better understanding of what motivates different forms of redundancy. Reference grammars of a 50-language variety sample were analyzed for the existence and communicative functions of four types of concord. The results show that argument concord and temporal concord are nearly universal, whereas only a subset of languages allow for negative concord and plural concord. Two functional principles are shown to motivate concord: the need to be precise, and the need to emphasize crucial information. These principles lead to distinct types of redundancy: The need to be precise results in accidental redundancy in the case of an obligatory grammatical marker, whereas the need to emphasize information invokes purposeful redundancy. The two types of redundancy are shown to be fundamentally distinct in their communicative nature as well as their characteristic diachronic development.